Digestible lysine requirement for European laying quail (Acta Scientiarum. Animal Sciences, 2019)
The experiment was carried out to evaluate the productive performance of European quails (Coturnix coturnix) in the production phase, fed with diets containing different levels of digestible lysine. A total of 175 female quails, aged 65 days, were randomly distributed in a completely randomized design with five treatments and five replicates per treatment. The animals were housed in 25 metal cages, and each cage represented an experimental parcel, with seven birds per parcel. The birds were fed the experimental rations containing 1.177, 1.217, 1.317, 1.417, and 1.517% digestible lysine. The parameters evaluated were: laying rate, mass of eggs produced, feed intake in the period, lysine intake, feed conversion per dozen and per mass. Significant differences were observed for posture rate with quadratic behavior, which indicated higher production for the level of 1.23% of digestible lysine. There was an increasing linear behavior for the feed and lysine intake, and for conversion feed per dozen and by mass, we observed quadratic behaviors. This indicates better feed conversion index when the optimal inclusion level was 1.33% and 1.404% of digestible lysine in the diet, respectively. The requirement of digestible lysine in diets for European quails is 1.404%, which corresponds to a daily intake of 421.20 milligrams of digestible lysine.